79.2k views
10 votes
HELP!!!!PLEASEEEEEE JUST PLEASEEEEE!!!!!

HELP!!!!PLEASEEEEEE JUST PLEASEEEEE!!!!!-example-1

2 Answers

10 votes

Answer:

y =
((x w -a))/(r)

Explanation:

x w - y r = a

Take ( y r ) to right side.

x w = a + y r

Now take ( a ) to left side.

x w - a = y r

Now divide both sides by r.


((x w -a))/(r) =(yr)/(y)

So, the answer is :

y =
((x w -a))/(r)

User Jameskind
by
6.0k points
6 votes

Answer:

  • y = (xw - a)/r

Explanation:

Given equation:

  • xw - yr = a

Solve for y:

  • yr = xw - a
  • y = (xw - a)/r
User DjBo
by
5.4k points